The Zigzag Wingbox for a Span Morphing Wing - Saavedra-Flores, E (2013)
This paper presents the Zigzag wingbox concept that allows the wing span to be varied by 44% (22% extension and 22% retraction). The Zigzag wingbox consists of a rigid part and a morphing part. The rigid part is a semi-monocoque construction that houses the fuel tank and transfers the aerodynamic loads from the morphing part to the fuselage. The morphing part consists of various morphing partitions where in each partition there are two spars each consisting of two beams hinged together. Each morphing partition is covered by flexible skin and is bounded by two ribs through which the spars are connected. The ribs transfer the loads between the spars of adjacent morphing partitions and serves as the main structure to which the flexible skins are to be attached. The Zigzag wingbox concept is then incorporated in the rectangular wing of a medium altitude long endurance (MALE) UAV to enhance its operational performance and provide roll control. Equivalent modelling and preliminary sizing of the concept are performed to assess its feasibility and quantify its potential benefits. © 2012 Elsevier Masson SAS. All rights reserved.